The present educational practices of the Huks - Crisologo, Fortunato L. 1903- ([Quezon City University of the Philippines], 1953)
This study determines the present educational practices of the Huks. The study aims to know how the Huks, while they are engaged in a shooting war, educate themselves and spread their ideas and doctrines among the people. The topics discussed in this study are their educational objectives, their courses of study, their system of finance, their language medium of instruction, their administrative and organizational set-up, their teachers, and their teaching methods and procedures.
Thesis (M.Ed.)--University of the Philippines, 1953
Typewritten.
Vita
Keywords: Huks -- Education